Effects of carica papaya and punica granatum juice on sperm’s quality against high fat diet induced obesity in rats / Syarifah Faezah Syed Mohamad ...[et al]. - Syed Mohamad, Syarifah Faezah; Othman, Farah Amna; Ghazali, Farah Amalina; Khairul Kamal, Nurliyana (Universiti Teknologi MARA Cawangan Pahang, 2018)
Malaysia, known as Asia’s fattest country, recorded an increase in obesity rate, with the latest statistics in 2015 showing that more than half Malaysian population was diagnosed as obese and overweight. Thus, this study were conducted to determine anti obesity effects of Punica granatum and Carica papaya fruit juice and its effects on the sperm quality. Twenty Sprague Dawley rats were divided into four groups (n =5); normal group (NC), obese group (OG), P. granatum treatment group (PG) and C. papaya treatment group (CG). Rats in PG,CG and OG were induced to obesity using food pellets covered with butter. Fruit juices were given to PG and CG groups respectively, for 21 days (1ml/100g of b.wt). Sperm from epididymis were collected for the assessment of sperm count, morphology, motility, and viability. Relative body weight gain showed significant decreased in PG group on 7–14 days and 14–21 days(p ≤ 0.05). For sperm quality parameters, it showed non-significant results for all groups but positive trend was observed in PG with higher sperm count and viability compared to CG.The results suggested that consumption of fruit juices especially P. granatum did help in reducing body weight and increasing sperm quality in obese male rats